Retinal detachments in patients with AIDS and CMV retinopathy: a role for laser photocoagulation. - McCluskey, P (1995)
A retrospective review of all patients with a cytomegalovirus (CMV) related retinal detachment and HIV infection managed at the ocular immunology clinic at St Vincent's Hospital between January 1985 and June 1992 was performed. Over this period 142 patients with CMV retinopathy were managed and 17 eyes from 14 of these patients developed a retinal detachment related to CMV retinopathy. Fourteen eyes from 11 of these patients were treated surgically with combinations of laser photocoagulation, cryopexy, scleral buckling, vitrectomy, and silicone oil tamponade. The use of laser photocoagulation alone in five patients resulted in an excellent visual outcome. The majority of patients (90.9%) benefited from surgery in that vision was either stabilised or improved.